The world heroin market : can supply be cut? - Paoli, Letizia (Studies in crime and public policy., 2009)
Acknowledgements. 1. Introduction. Part I: The Development, Composition and Behavior of the World Opiate Market. 2. The Past as Prologue: The Development of the World Opiate Market and Rise of the International Control Regime. 3. 4. Did the Taliban's Ban Really Matter?. 5. Keeping Track of Opiate Flows. Part II: Country Studies. 6. Afghanistan and Burma: The Two Dominant Producers. 7. India: Diversion from Licit Cultivation. 8. Colombia: The Emergence of a New Producer. 9. Tajikistan: The Rise of a Narco-State. Part III: Policy Analysis and Implications. 10. The Theoretical and Practical Conse.